Non-breeding distribution and activity patterns in a temperate population of brown skua - Schultz, Hendrik; Hohnhold, Rebecca J.; Taylor, Graeme A.; Bury, Sarah J.; Bliss, Tansy; Ismar, Stefanie M. H.; Gaskett, Anne C.; Millar, Craig D.; Dennis, Todd E. (Marine Ecology Progress Series, 2018)
Brown skuas Catharacta antarctica lonnbergi breed across a broad latitudinal range from the Antarctic to temperate regions. While information on the non-breeding distribution and behaviour for Antarctic and subantarctic populations is known, no data exist for populations breeding at temperate latitudes. We combined geolocation sensing and stable isotope analysis of feather tissue to study the non-breeding behaviour of brown skuas from the temperate Chatham Islands, a population that was historically thought to be resident year-round. Analysis of 27 non-breeding tracks across 2 winters revealed that skuas left the colony for a mean duration of 146 d, which is 64% of the duration reported for Antarctic and subantarctic populations from King George Island, South Shetland Islands, and Bird Island, South Georgia. Consistent with populations of brown skuas from Antarctica and the Subantarctic, the distribution was throughout mixed subtropical-subantarctic and shelf waters. Stable isotope analysis of 72 feathers suggests that moulting takes place over mixed subtropical-subantarctic and subtropical shelf waters. We conclude that brown skuas from the Chatham Islands are migratory, but the year-round mild environmental conditions may reduce the necessity to leave their territories for extended periods.